An AAV Vector for Inducible Gene Expression Preferentially in Muscles - Renping Zhou; Yicong Le; Zhengyun Jiang; Xi Zheng; Christina Marinaro; Suzie Chen; Bing Wang; Suqing Zhao; Min Chen; Philip Furmanski; Kun Zhang (International Journal of Genetic Modifications and Recombinations, 2023)
Adeno associated viral (AAV) vectors has been used widely in gene therapy and efforts have been made to improve their utility by adding genetic elements that would enable targeting transgene expression to particular cells or tissues of interest and permitting on/off regulation of expression. In this study, we designed a recombinant AAV9 variant PHP.eB vector with muscle creatine kinase (Mck)-derived enhancers, a synthetic muscle-expression promoter, in combination with a third-generation tetracycline-inducible promoter, to drive expression of reporter genes luciferase and GFP (PHP.eB-Pmus-TetOn-teLuc and PHP.eB-Pmus-TetOn-eGFP, respectively). This recombinant vector expresses genes at high levels preferentially in muscle cells, that can be controlled by doxycycline (Dox) exposure both in vitro and in vivo. To test inducibility of these vectors in vivo, adult SKH hairless mice were injected intravenously with 2x1012 virus genomes. Dox-containing food (625 mg/kg) was given 1 day after virus injection to initiate expression. After one month, tissue luciferase activity was assayed. Luciferase expression level per viral genome in muscle tissues including biceps brachii, biceps femoris, and heart tissue were higher in Pmus-TetOn group. Long-term expression was also assessed for the PHP.eB-Pmus-TetOn-teLuc vector: two weeks after virus injection and Dox induction, Dox-containing food was replaced with conventional diet and luciferase expression was tracked biweekly using IVIS in vivo imaging. Following Dox removal, luciferase expression decreased and by 6 weeks had returned to basal levels. Re-exposure to Dox stimulated luciferase expression to levels similar to the first Dox-induced expression. Removal of the second Dox stimulus resulted in slow loss of luciferase activity, which could again be re-induced by Dox exposure. These experiments indicate that this inducible, tissue-selective expression could be maintained in vivo for at least 18 weeks.
Keywords: AAV; Gene therapy; Tet-on; inducible gene expression; muscle specific promoter